Lewis & Clark : [videorecording (DVD)] : great journey West - Neibaur, Bruce; Truitt, Lisa; Miller, Jeff T.; Richards, Mose; Bridges, Jeff, 1949- (National Geographic Video, 2002)
Relive an amazing tale of discovery and exploration as National Geographic brings to life the first crossing. Two hundred years after Lewis & Clark epic journey, go back in time and discover the adventure, danger, and beauty of the unmapped West.